Studies on the transmission of malignant catarrhal fever in experimental animals: A serial infection of cattle and buffalo by means of whole blood inoculation - Agus Wiyono; Rini Damayanti (Indonesian Center for Animal Research and Development (ICARD), 1999)
Malignant catarrhal fever (MCF) is a fatal disease especially affecting cattle and buffaloes. A study on the serial blood transmission of MCF was conducted by injecting whole blood of MCF animals into 9 experimental animals. Diagnosis of MCF was based on the clinico-pathological fmdings and polymerase chain reaction (PCR) test. The disease has successfully, been achieved in six animals of three Bali cattle and three buffaloes but not in a Bali-cross breed and two Bos indicus (Ongole) cattle. Wide range of clinical signs and gross-pathological features were observed. The study showed the degree of susceptibility of experimental animals: Bali cattle and buffalo were highly susceptible (3 out of 3 affected with MCF), Bali-cross breed and Bos indicus (Ongole) cattle seemed not susceptible to whole blood experimental transmission. It shows that when Bali cattle acted as inoculum donor, buffalo tended to be clinically more severe than Bali cattle. On the other hand, when buffalo acted as inoculum donor, Bali cattle suffered from MCF more severe than buffalo. The diagnosis of MCF by histopathological examination and the PCR test bad positive correlation (100%) in the first experiment, while in the second experiment the PCR test tends to be more sensitive. Based on the restriction endonuclease (RE) test, the MCF causal agent in this study appeared to be genetically similar in each case. It is concluded that the serial experimental transmission of MCF by means of whole blood inoculation has been successfully achieved in Bali cattle and buffalo but not in Bali-cross breed and Ongole cattle, and there is a positive correlation between the PCR test and histopathological examination with the PCR test tends to be more sensitive. Key words: MCF, serial transmission, blood, cattle, buffalo, Indonesia